2017
DOI: 10.1007/s10802-016-0254-5
|View full text |Cite
|
Sign up to set email alerts
|

Father Participation in Child Psychopathology Research

Abstract: The purpose of the current study was two-fold: (1) To examine time trends of the inclusion of fathers in child psychopathology research from 2005 to 2015; and (2) to examine online crowdsourcing as a method to recruit and study fathers. In study 1, findings indicated that, relative to two earlier reviews of father participation from 1984 – 1991 and 1992 – 2004, there has been limited progress in the inclusion of fathers in child psychopathology research over the last decade. In study 2, without explicit effort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(74 citation statements)
references
References 61 publications
3
71
0
Order By: Relevance
“…Prior research has convincingly demonstrated that data obtained via crowdsourcing methods are as reliable and valid as those obtained via more traditional data collection methods (e.g., Buhrmester, Kwang, & Gosling, 2011; Casler, Bickel, & Hackett, 2013). Recently, research has also demonstrated reliability and validity of crowdsourcing methods for child and family studies (Parent, Forehand, Pomerantz, Peisch, & Seehuus, in press). …”
Section: Methodsmentioning
confidence: 99%
“…Prior research has convincingly demonstrated that data obtained via crowdsourcing methods are as reliable and valid as those obtained via more traditional data collection methods (e.g., Buhrmester, Kwang, & Gosling, 2011; Casler, Bickel, & Hackett, 2013). Recently, research has also demonstrated reliability and validity of crowdsourcing methods for child and family studies (Parent, Forehand, Pomerantz, Peisch, & Seehuus, in press). …”
Section: Methodsmentioning
confidence: 99%
“…Parents were recruited online through Amazon's Mechanical Turk (MTurk) as part of a larger study on the assessment of parenting. MTurk is the dominant crowdsourcing application in the social sciences (Chandler, Mueller, & Paolacci, ), and prior research has convincingly demonstrated that data obtained via crowdsourcing methods are as reliable as those obtained via more traditional data collection methods for adult populations (e.g., Buhrmester, Kwang, & Gosling, ; Casler, Bickel, & Hackett, ; Paolacci & Chandler, ; Shapiro, Chandler, & Mueller, ) as well as specifically for child psychopathology research (Parent, Forehand, Pomerantz, Peisch, & Seehuus, ; Schleider & Weisz, ). On MTurk, parents responded to a study on parenting that was listed separately for three age groups to ensure roughly equal sample sizes in these three age ranges: young childhood (3 to 7 years old), middle childhood (8 to 12 years old), and adolescence (13 to 17 years old).…”
Section: Methodsmentioning
confidence: 99%
“…This pattern might be due to mothers' unique position in child development, including their common role as "primary caregiver" [45,51], but also prenatal influence [27], or the higher prevalence of depression in women [37]. At the same time, the relative lack of research on paternal influences makes these patterns difficult to interpret [46]. The few studies on father-offspring transmission indicate, however, that paternal depressive symptoms may be uniquely associated with their child's internalizing symptoms as well [5,31].…”
Section: Gender-specific Transmission Of Internalizing Symptomsmentioning
confidence: 99%